ENT530: Management and services of Muslim cemetery in Klang valley area / Nur Afiqah Nadhirah Khairsiddik. - Khairsiddik, Nur Afiqah Nadhirah; Mohd Rosli, Aimie Diyanna; Ghazali, Intan Izzati; Mohd Shafridin, Mohd Shamirul (2019)
To provide management and services for the Muslim Cemetery in Klang Valley area. To be able to manage Muslim Cemetery for the entire Malaysia region and provides excellent services.